The challenge of managing stress versus distress; Strength training for long-distance triathletes: theory to practice - Kraemer, W.; Nitka, M. (Strength and Conditioning Journal, 2021)
Being aware of factors that contribute to stress that can lead to "distress" is the first step in optimizing an athlete`s environment for optimal training and performance. Distress is the body`s inability to successfully cope with external stressors. Whether from a physical perspective of "too much too soon" or nonfunctional overreaching in a conditioning program or from environmental challenges of heat or from psychological challenges related to depression, awareness, assessment, and actions are needed to ensure an athlete`s health and wellness. Factors such as nutritional deficiencies and reduced recovery between sessions may increase overall stress possibly leading to overreaching, overtraining, and overuse. Because of the highly individual responses to both training and outside stressors, individualization of programs, monitoring, and interventions are needed. Ultimately, managing athlete stress is a "team approach."; Concurrent training, commonly acknowledged as a training method where strength and endurance training are completed complementary to each other, is a strategy often implemented in endurance cyclists' and runners' programs to improve physiological determinants of success such as exercise economy. Although concurrent training methods and strategies have been examined to a large extent in endurance cyclists and runners, literature examining optimal concurrent training methods to improve physiological variables in long-distance triathletes is minimal, leaving optimal programming relatively unknown. This practical applications paper identifies and outlines current concepts and considerations regarding concurrent training for long-distance triathletes including mechanisms contributing to improved performance, muscle and movement patterns used, exercise selection, load, velocity of movement, scheduling, frequency, and duration of training. Common misconceptions related to concurrent training are also identified and practical considerations for the application of concurrent training for coaches, athletes, and other professionals to improve all 3 disciplines of triathlon are discussed.